The Antara Berpikir Matematis dan Matematika: Strategi Pemecahan Masalah pada Mahasiswa Pendidikan Guru Sekolah Dasar - Kurniati, Nurdiyah; Andi Asrafiani Arafah; Fitri Aida Sari (Mandalika Mathematics and Educations Journal, 2025)
Problem-solving ability is a fundamental skill that students must have, especially to meet the demands of 21st-century competencies. However, students' thinking process performance in solving mathematical problems is still relatively low. Therefore, this study aims to identify variations in prospective teachers' thinking processes as an important component in determining student performance. This research is qualitative research by applying a case study approach. The subjects in this study were 29 prospective elementary school teacher students at one of the universities in Borneo. The test instrument used was a description test of 6 questions. The data analysis was conducted through data condensation, data presentation, and conclusion drawing. From the analysis process, the results showed that the problem-solving ability was still not optimal. The thinking process applied by students only tends to certain topics. For the mathematical thinking process, the strategy used is the application of the combination formula and SPLDV. As for the mathematical thinking process, the strategies used are organizing data, listing possibilities, guessing and fixing, eliminating unqualified, working backward, and looking for patterns. Thus, it can be concluded that students can think both mathematically and mathematically in solving mathematical problems.